Fundamentals of modern photography. - Ang, Tom, ....- (London : Octopus, 2009)
The key features include the basics of photography, such as the nature of light, lens construction, and fundamental concepts, as well as sections on film, cameras, accessories, processing, and all other aspects of digital photography - from image capture to output. The book also deals with important subjects usually ignored in manuals, including critical theory, how to present images, ethical issues, and copyright. Practical exercises and summaries are included in each chapter, providing a complete set of tutorials.
Keywords: Fotografie